Inorganic nitrogen uptake rate of Picea asperata curtailed by fine root acclimation to water and nitrogen supply and further by ectomycorrhizae. Issue 4 (4th October 2021) - Xie, Lulu; Zhou, Xingmei; Liu, Qinghua; Zhao, Chunzhang; Yin, Chunying
Abstract: Ectomycorrhizal (ECM) fungi colonization and function depend on soil water and nutrient supply. To study the effects of resource supply on ECM colonization and inorganic nitrogen (N) uptake by roots of Picea asperata seedlings, we conducted a study at the end of a 5‐year long experiment consisting of five watering regimes (40, 50, 60, 80, and 100% of field capacity) and three NH4 NO3 application rates (0 [N0], 20 [N1], and 40 [N2] g N m −2 year −1 ). We measured fluxes of ammonium ( NH 4 + ) and nitrate ( NO 3 − ) into colonized and uncolonized roots using noninvasive microtest technology. We found that, across the N supply levels, ECM colonization rate increased by 53 ± 14% from the highest to the lowest level of water supply. Across the watering regimes, the fraction of mycorrhizal root tips was 39 ± 4% higher under native N supply compared to roots grown under N additions. As expected for conifers, both colonized and uncolonized roots absorbed NH 4 + at a higher rate than NO 3 − . N additions reduced the instantaneous ion uptake rates of uncolonized roots grown under low water supply but enhanced the fluxes into roots grown under sufficient soil water availability. Soil water supply improves inorganic N uptake by uncolonized roots but reduces the efficiency of colonized roots. Under the lowest water supply regime, the uptake rate of NH 4 + and NO 3 − by colonized roots was 40–80% of those by uncolonized roots, decreasing to 20–30% as soil water supply improved. Taken together, our results suggest that the role ectomycorrhizae play in the nutrient acquisition of P. asperata seedling likely diminishes with increasing availability of soil resources.